2020
DOI: 10.1038/s41467-020-14387-w
|View full text |Cite|
|
Sign up to set email alerts
|

Endothelial progeria induces adipose tissue senescence and impairs insulin sensitivity through senescence associated secretory phenotype

Abstract: Vascular senescence is thought to play a crucial role in an ageing-associated decline of organ functions; however, whether vascular senescence is causally implicated in age-related disease remains unclear. Here we show that endothelial cell (EC) senescence induces metabolic disorders through the senescence-associated secretory phenotype. Senescence-messaging secretomes from senescent ECs induced a senescence-like state and reduced insulin receptor substrate-1 in adipocytes, which thereby impaired insulin signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 55 publications
(66 reference statements)
9
69
0
Order By: Relevance
“…However, the inverse relationship could also be discussed since it was recently shown that endothelial dysfunction, through secreted factors, may directly alter adipose tissue homeostasis and lead to insulin resistance [54]. Direct evidence that endothelial cell senescence induces adipose tissue metabolic dysfunction and systemic insulin resistance was recently demonstrated in Tie2-TERF2DN-Tg mice, which display an endothelium-specific form of progeria [55].…”
Section: Discussionmentioning
confidence: 99%
“…However, the inverse relationship could also be discussed since it was recently shown that endothelial dysfunction, through secreted factors, may directly alter adipose tissue homeostasis and lead to insulin resistance [54]. Direct evidence that endothelial cell senescence induces adipose tissue metabolic dysfunction and systemic insulin resistance was recently demonstrated in Tie2-TERF2DN-Tg mice, which display an endothelium-specific form of progeria [55].…”
Section: Discussionmentioning
confidence: 99%
“…We recently generated EC-specific progeroid mice that overexpress the dominant-negative form of telomeric repeat-binding factor 2 (TRF2DN) under the control of Tie2 or vascular endothelial cadherin (VEcad) promoter (Barinda et al , 2020). By utilizing these EC-specific progeroid mice, we investigated the role of EC senescence in pulmonary hypertension (PH).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we have revealed a crucial role of senescent ECs in the progression of PAH through the interaction with PASMCs via Notch-mediated juxtacrine signaling. EC senescence has been considered to play a causative role in age-related metabolic (Shosha et al , 2018; Barinda et al , 2020) and cardiovascular disease (Minamino et al , 2002; Ahmad et al , 2015; Yamazaki et al , 2016; Shakeri et al , 2018; Song et al , 2020). Moreover, the potential role of cellular senescence has been explored in various non-age-related diseases such as type-1 diabetes (Thompson et al , 2019) and PAH associated with congenital heart disease (Van Der Feen et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that chronic SASP is the major contributor to aging associated organ dysfunction induced by senescent cells [14,15]. Cytokines, matrix remodeling enzymes, and extracellular vesicles have all been identified in senescent cell secretions, however the exact profile can change depending on the stressor [14,16,17].…”
Section: Sasp Regulation and The Secretory Phenotype Of Senescent Vasmentioning
confidence: 99%
“…Specifically, this includes insults to the cardiovascular system such as, atherosclerosis, diabetes, and heart failure [13]. SASP transmits persistent sterile inflammation that is associated with age-related chronic diseases and frailty, thus providing a novel therapeutic opportunity [14,15].…”
Section: Introductionmentioning
confidence: 99%